Perbedaan Kinerja Keuangan dengan Menggunakan Metode Eva (Economic Value Added) dan MVA (Market Value Added) pada Industri Pertambangan Minyak dan Gas Bumi yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017) - Anisah Ulfah (Science of Management and Students Research Journal (SMS), 2020)
The EVA (Economic Value Added) Method (X1) and Market Value Added (X2) in the Oil and Gas Mining Industry Registered on the Indonesia Stock Exchange for the period 2013-2017. The research population is the Oil and Gas Mining Industry Company Listed on the Indonesia Stock Exchange with the 2013-2017 research period. Samples were selected using the Purposive Sampling method (sampling is based on certain considerations) so that the sample is 3 samples. Data is obtained based on the publication of the Indonesia Stock Exchange (IDX). The variables used are EVA (Economic Value Added) and MVA (Market Value Added) methods as independent variables, Financial Performance as the dependent variable. Hypothesis testing using the Independent t-Test. The results of this study prove that there is no difference after using the EVA method with a sign value. t = 0,622> 0,05, there are differences after the MVA method is used with the sign value.  t = 0,020 <0,05. The highest average EVA value is found at PT. Ratu Prabu Energi, Tbk in the amount of  Rp. 36.904.667.845, Tbk and the lowest average EVA is at PT. Elnusa, Tbk  Rp. 9.366.363.561, while the highest average MVA was found at PT. Elnusa, Tbk  Rp. 6.058.598.402.800  and the lowest MVA average is at PT. Radiant Utama Interinsco, Tbk for Rp. 179.944.652.875  and it can be concluded based on the table above that the average increase in financial performance using the MVA method is greater than the EVA method in the oil and gas mining industry listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017.